Arquitetura como direito: proposta de escritório modelo em assistência técnica à habitação de interesse social na baixada do Marco em Belém do Pará - REIS, Carlos André de Sousa (2023)
The socio-spatial inequality is one of the most striking indicators of the differences in Brazil, the city centers, where infrastructure, work and services are concentrated, are intended for the highest income classes, while low-income families are restricted to peripheral and environmentally fragile areas. Belém, like any other large Brazilian urban center, reflects that in the organization of its territory, with the peculiarity that the place where the city is inserted is drained by a large amount of urban rivers, these areas are vectors of the poorer population that find in these regions a way of living near the center. These territories are known as lowland areas (baixadas in Portuguese) and are characterized by low elevation terrain, moist and constantly flooded terrain, unconsolidated soil with high population and constructive density, low income medium and with high quantitative and qualitative housing deficit. Throughout history many housing policies and programs have been implemented to try to reduce this deficit, one of them was Law N°. 11888/2008, which states that states and municipalities should provide families with incomes below three minimum wages for free public technical assistance, for housing design and construction, however, the public sector faced difficulties in implementing the law and bringing this right to architecture for this population. This work intends to make a preliminary study to the installation of a model office in Technical Assistance, having as focus area of the study the lower of the Marco neighborhood in Belém do Pará.